ANALYSIS DIFFERENTIATED ASSESSMENT INSTRUMENT FOR GRADE 9 JUNIOR HIGH SCHOOL IN EMANCIPATED CURRICULUM - Sukmastiani, Kadek Swasty; Budiarta, Luh Gd Rahayu; Utami, Ida Ayu Made Istri (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
In the implementation of the curriculum, of course, it cannot be separated from assessment activities. Assessment helps teachers to know the ability and understanding of students in receiving material. The government is very aggressive in creating a new curriculum to catch up on what was missed in the previous curriculum. Currently, the government has published the latest curriculum with the name Emancipated Curriculum. This curriculum has several assessments that are similar to the previous curriculum. The assessments in question are diagnostic assessments, formative assessments, and summative assessments. This assessment aims to help develop differentiated assessment in schools and in accordance with the diverse learning styles of students. This research uses the Design and Development or D&D method proposed by Richey and Klein's (2007). There are four stages in product development, namely Analysis, Design, Development, and Evaluation or called ADDE. Data collection was conducted at SMPN 1 Seririt, with 38 respondents divided into 37 students and 1 English teacher. The resulting data were analyzed with mixed methods or a mixture of qualitative and quantitative. The result of this research is a product in the form of an assessment book intended for teachers. This manufacturing process is based on the ADDE method (Analysis, Design, Development, and Evaluation).